Analysis of data on cyanobacteria and cyanotoxins in public supply reservoirs (São Paulo, Brazil) - De Souza Bronstein, Caroline Augusta [UNESP]; Moschini-Carlos, Viviane [UNESP] (Uniwersytet Gdanski, 2024)
The incidence of cyanobacterial blooms in reservoirs intended for human supply represents a serious health risk due to the ability of these organisms to produce cyanotoxins. The study aimed to collect and summarize information related to variables associated with eutrophication of water sources of the Sorocaba River basin (São Paulo, Brazil). The objective was to assess the occurrence of cyanotoxins in treated water supplied to approximately 800,000 people. The study analyzed data from different abstraction, treatment, and distribution stations, emphasizing the supply from the Itupararanga and Ipanema dams, as well as the Sorocaba River. Data were obtained from the Drinking Water Quality Surveillance Information System (SISAGUA), the Autonomous Water and Sewage Service (SAAE), and the Environmental Company of the State of São Paulo (CETESB). A total of 4719 data points for cyanobacteria, chlorophyll-a, and cyanotoxins were analyzed between 2014 and 2021. The results indicate a deterioration in the trophic state of the Sorocaba River and the Itupararanga Dam, revealing a correlation between cyanobacteria and saxitoxins, with a predominance of the genus Raphidiopsis. A microcystin concentration of 0.40 μg l-1 was recorded at the Itupararanga Dam in treated water.
Keywords: cyanobacteria; cyanotoxins; eutrophication; public health; reservoirs